PENGARUH PENGGUNAAN INFORMASI AKUNTANSI, PEMANFAATAN TEKNOLOGI INFORMASI DAN MODAL PINJAMAN TERHADAP KINERJA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Yulis, Yul Emri; Andriani, Rina; Diskhamarzaweny, Diskhamarzaweny; Sepridawati, Yeni; Irwan, Muhammad (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to see the effect of variable X on variable Y, variable x in this study is the use of accounting information, utilization of information technology, and loan capital, while variable Y is the performance of MSMEs in Kec. Kuantan Tengah, Kuantan Singingi Regency. The number of samples in this study was 100 MSME actors. Data was collected using a questionnaire, then the data was processed using SPSS. The results of the study stated that the variables of the use of information accounting, utilization of information accounting, and loan capital had a significant effect on the performance variable of MSMEs in Kec. Kuantan Tengah, Kuantan Singingi Regency. The results of this study provide several important directions for MSMEs. These results show the importance of understanding and using accounting information in routine business decision-making, especially in financial planning and cost control.